(3TQM GdcaGjIs - (3GdfLaj, GHf cGTa GdZWGA, Ydj Hf eMeO QVG Hf ehSi, J HYO (B1354(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3bhdg GdYGTQ GdZQV ef gPG GdJfHjg gh HjGf YOe GYJHGQ chf GdeSJUMH YfO Gdjbjf Hg PG Mce TQYj Ch faS GdMce GdTQYj hEfg jTJQW ajg Pdc aj ReGf GdTc adh cGf GdTjA aj ReGf GdTcs
(3BNQgG (B:s
(3BNQgG(B: (3Hd jMJed aj cd eRjI Cfg dG ONd dgG aj hCf GdJQLjM HgG ef bHjd GdJQLjM HdG eQLM adG jchf CKQ dPj GdeRjI GUdGs
(3GdfSNI YHGQI Yf eShOI GdeDdas
(3JHUQI GdeDda (B:s
(3PcQ GdRQcdj haGJg SfI (B1350(3g`, ZjQ Cfg cGf MjG SfI (B1354(3, hab eG PcQg aj fgGjI GdLRA GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 19s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs